Unveiling the Cosmic Chemistry: Revisiting the Mass–Metallicity Relation with JWST/NIRSpec at 4 < z < 10 - Arnab Sarkar; Priyanka Chakraborty; Mark Vogelsberger; Michael McDonald; Paul Torrey; Alex M. Garcia; Gourav Khullar; Gary J. Ferland; William Forman; Scott Wolk; Benjamin Schneider; Mark Bautz; et al. (The Astrophysical Journal)
We present star formation rates (SFRs), the mass–metallicity relation (MZR), and the SFR-dependent MZR across redshifts 4–10 using 81 star-forming galaxies observed by the JWST NIRSpec employing both low-resolution PRISM and medium-resolution gratings, including galaxies from the JWST Advanced Deep Extragalactic Survey (JADES) GOODS-N and GOODS-S fields, the JWST-PRIMAL Legacy Survey, and additional galaxies from the literature in the A2744, SMACS-0723, RXJ2129, BDF, COSMOS, and MACS1149 fields. These galaxies span a 3 dex stellar mass range of 10 ^7 < M _* / M _⊙ < 10 ^10 , with an average SFR of 7.2 ± 1.2 M _⊙ yr ^−1 and an average metallicity of $12+log({\rm{O}}/{\rm{H}})=7.91± 0.08$ . Our findings align with previous observations up to z = 8 for the MZR and indicate no deviation from the local Universe fundamental metallicity relation (FMR) up to this redshift. Beyond z = 8, we observe a significant deviation (∼0.27 dex) in FMR, consistent with recent JWST findings. We also integrate Cosmic Evolution Early Release Science (135 galaxies) and JADES (47 galaxies) samples with our data to study the metallicity evolution with redshift in a combined sample of 263 galaxies, revealing a decreasing metallicity trend with a slope of 0.067 ± 0.013, consistent with IllustrisTNG and EAGLE but contradicting the FIRE simulations. We introduce an empirical mass–metallicity–redshift relation: $12+{\rm{log}}({\rm{O}}/{\rm{H}})=6.29+0.237$ × $log(M_{* }/M_{\odot })-0.06× (1+z)$ , which accurately reproduces the observed trends in metallicity with both redshift and stellar mass. This trend underscores the “Grand Challenge” in understanding the factors driving high-redshift galactic metallicity trends, such as inflow, outflow, and active galactic nucleus/stellar feedback—and emphasizes the need for further investigations with larger samples and enhanced simulations.